Effect of corneal allogenic intrastromal ring segment (cairs) implantation surgery in patients with keratoconus according to prior corneal cross-linking status - Yücekul, Burcu; Tanrıverdi, Cafer; Taneri, Suphi; Keskin Perk, Fatma Feyza Nur; Karaca, Yiğit; Kılıç, Aylin (My University, 2024)
PURPOSE: To compare the effects of corneal allogenic intrastromal ring segment (CAIRS) implantation on topographical measurements and visual outcomes of patients with keratoconus with and without corneal cross-linking (CXL) prior to the time of implantation. METHODS: Sixty-seven eyes with corneal allograft intrastromal ring segment implantation (KeraNatural; Lions VisionGift) due to advanced keratoconus were included in the study. Thirty-seven eyes had no CXL and 30 eyes had had CXL before being referred to the authors. The changes in spherical equivalent (SE), uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), steep keratometry (K1), flat keratometry (K2), mean keratometry (Kmean), maximum keratometry (Kmax), and thinnest pachymetry were retrospectively analyzed 6 months after the implantation. RESULTS: The median age was 29 years in the CXL group and 24.0 years in the non-CXL group (P > .05), respectively. All topographical and visual parameters before implantation were similar in both groups (P > .05 for all parameters). At 6 months, CDVA, K1, and Kmean showed higher improvement in the non-CXL group than the CXL group (P = .030, .018, and .039, respectively). CONCLUSIONS: CAIRS surgery has a flattening effect on both the corneas with and without CXL. The cornea with prior CXL treatment had less flattening effect due to the stiffening effect of prior CXL.
Keywords: Corneal Cross-Linking; Corneal Pachymetry; Corneal Stroma; Corneal Topography; Corneal Transplantation; Photochemotherapy; Photosensitizing Agents; Riboflavin; Ultraviolet Rays; Visual Acuity